Effectiveness of back massage on sleep pattern among patients with congestive cardiac failure - Amol Sable; Thangaraj Sivabalan; Akshaya Narayan Shetti (Wolters Kluwer Medknow Publications, 2017)
Background: Sleep plays an important role in congestive cardiac failure (CCF). Back massage reduces anxiety, discomfort, and physical suffering in CCF patients. Study objective is to assess sleep pattern in CCF patients before and after back massage. Materials and Methods: A quasi-experimental study was conducted in Pravara Rural hospital, Loni, India over 4 months in 2016. Thirty CCF patients were included in the study with purposive sampling. Nurse investigator performed 20-min back massage thrice daily, 5 min for each step from the day of admission till discharge. In back massage, effleurage, stroking, kneading, and assessment of effectiveness was recorded using the Pittsburg sleep quality index. Results: Thirty CCF patients were included, out of which individuals aged >65, 56-65, and 35-45 years age group were 40%, 24%, and 13%, respectively. Twenty-four had left and 6 had right heart failure. Distribution of mean and standard deviation of pretest for sleep quality was 9.50 (3.14), indicating poor sleep quality. Posttest, the mean score was 4.47 (0.89), indicating good quality sleep. Eleven patients had >8 h of sleep, 15 patients had 6-8 h of sleep, whereas 4 patients had less than 6 h of sleep pretest. Posttest, 22 patients had >8 h and the remaining had 6-8 h of sleep. Conclusions: Back massage technique is safe and cost-effective in CCF patients, by which the quality and duration of sleep is improved. It can be a part of the standard treatment.